The fox and the grapes - UNK (New Delhi My kids world, 2015)
A hungry fox tried to reach some grapes hanging high on a vine. After failing several times, he gave up and said the grapes were probably sour. Moral: It$1 (Bs easy to dislike what you can$1 (Bt have.s
Keywords: English